Phosphorus fractions under different land-use systems in oxisols of the Brazilian cerrados - Westerhof, R; Silva, J.E. da; Ayarza, Miguel Angel; Zech, W. (International Center for Tropical Agriculture, 1999)
We examined whole-soil samples and particle-size fractions to study the distribution of different phosphorus (P) fractions after land-use change from native savanna to crops, pasture, and reforestation on clayey and loamy Oxisols of the Brazilian savannas. Phosphorus was extracted sequentially, according to a modified Hedley procedure, into inorganic and organic P (NaOH-extractable Pi and Po, respectively), and recalcitrant P (P HCl and P res). Under natural conditions of strong P deficiency, over 60% of NaOH-extractable P was organic, reflecting the high contribution of P. to plant nutrition. Fertilization elevated inorganic P forms but had only small effects on Po. The increase of inorganic P forms from fertilizer P was greatest in the P, and lowest in the fractions. After fertilization, the reforested sites maintained high NaOH-extractable P through efficient recycling, whereas at the crop and pasture sites, P tended to accumulate in recalcitrant forms. Possibly, the adsorption of P to oxyhydroxides was reduced at the more acid reforested sites by complexation of Fe and Al oxides with organic acids. The ratio of NaOH-extractable P. to P. appeared to effectively reflect the P status of the land-use systems, and P deficiency increased in ascending order from native savanna > pasture > reforestation > crop, independently of soil type.